The VLTi/PIONIER survey of southern TTauri disks†. Issue Volume 8:Issue S299(2013) (6th January 2014) - Anthonioz, Fabien; Ménard, F.; Pinte, C.; Thi, W-F.; Lebouquin, J.-B.; Berger, J.-P.; Benisty, M.; Absil, O.; Duchène, G.; Lazareff, B.; Malbet, F.; Millan-Gabet, R.; et al.
Abstract: Studying the inner regions of protoplanetary disks (1-10 AU) is of importance to understand the formation of planets and the accretion process feeding the forming central star. Herbig AeBe stars are bright enough to be routinely observed by Near IR interferometers. The data for the fainter T Tauri stars is much more sparse. In this contribution we present the results of our ongoing survey at the VLTI. We used the PIONIER combiner that allows the simultaneous use of 4 telescopes, yielding 6 baselines and 3 independent closure phases at once. PIONIER's integrated optics technology makes it a sensitive instrument. We have observed 22 T Tauri stars so far, the largest survey for T Tauri stars to this date. Our results demonstrate the very significant contribution of an extended component to the interferometric signal. The extended component is different from source to source and the data, with several baselines, offer a way to improve our knowledge of the disk geometry and/or composition. These results validate an earlier study by Pinte et al . 2008 and show that the dust inner radii of T Tauri disks now appear to be in better agreement with the expected position of the dust sublimation radius, contrary to previous claims.